1973
DOI: 10.1172/jci107385
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Adrenal Ornithine Decarboxylase by Adrenocorticotropic Hormone and Cyclic AMP

Abstract: A B S T R A C T Adrenal ornithiine decarboxylase activity was stimulated in a dose-related manner after administration of ACTH or dibutyryl (6N-2'-O-dibutyryl) cyclic AMP to hypophysectomized rats. Little effect was observed for 2 h, but striking increases in enzyme activity were observed 4 h after administration of these substances. Effects of ACTH and dibutyryl cyclic AMP were not secondary to stimulation of steroidogenesis, since hydrocortisone had no effect on adrenal ornithine decarboxylase although it di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
2

Year Published

1975
1975
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 23 publications
3
13
2
Order By: Relevance
“…The ornithine decarboxylase (ODC) activity of the prostate is stimulated by testosterone (Pegg et al 1970), that of the rat uterus or chick oviduct is stimulated by estradiol (Cohen et al 1970; Kaye et al 1971;Villee and Loring 1975), that of the liver is stimulated by growth hormone (Janne and Raina 1969), and that of the adrenal is stimulated by adrenocorticotropic hormone (Richman et al 1973). Ovarian ODC activity rises sharply during the pre-ovulatory surge of luteinizing hormone (Kobayashi et al 1971), and the rise of activity can be prevented by the injection of anti-LIT before proestrus.…”
mentioning
confidence: 99%
“…The ornithine decarboxylase (ODC) activity of the prostate is stimulated by testosterone (Pegg et al 1970), that of the rat uterus or chick oviduct is stimulated by estradiol (Cohen et al 1970; Kaye et al 1971;Villee and Loring 1975), that of the liver is stimulated by growth hormone (Janne and Raina 1969), and that of the adrenal is stimulated by adrenocorticotropic hormone (Richman et al 1973). Ovarian ODC activity rises sharply during the pre-ovulatory surge of luteinizing hormone (Kobayashi et al 1971), and the rise of activity can be prevented by the injection of anti-LIT before proestrus.…”
mentioning
confidence: 99%
“…This response is of particular interest because the enzyme is rate-limiting in the synthesis of polyamines (10), which are implicated in the control of tissue growth (11)(12)(13). Because accumulation of cyclic AMP temporally precedes changes in ornithine decarboxylase activity and cyclic AMP analogues reproduce the hormonal effect, a cyclic AMP-dependent mechanism has been postulated for hormonal regulation of ornithine decarboxylase activity (1)(2)(3)(4)(5). Furthermore, cyclic AMP-dependent protein kinase (ATP:protein phosphotransferase, EC 2.7.1.37) has been implicated in the stimulation of ornithine decarboxylase by trophic hormones (14).…”
mentioning
confidence: 99%
“…In another series of mutant subclones, Yl(Kin), cyclic AMP-dependent protein kinase activity in cytosol fractions 1 …”
mentioning
confidence: 99%
“…Recent studies have shown that dibutyryl-adenosine 3': 5'-cyclic monophosphate can induce ornithine decarboxylase activity in the adrenal medulla and in numerous rat tissues (19)(20)(21)(22)(23). Further, it has been shown that cold exposure which leads to cholinergic stimulation of the adrenal medulla of the rat results in a marked increase in adenosine 3': 5'-cyclic monophosphate (cAMP) levels, followed by a rapid increase in ornithine decarboxylase activity (24,25).…”
mentioning
confidence: 99%